2012
DOI: 10.1111/j.1440-1843.2012.02255.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive function in obstructive sleep apnoea: A meta‐review

Abstract: Adult obstructive sleep apnoea (OSA) is associated with cognitive dysfunction. While many review articles have attempted to summarize the evidence for this association, it remains difficult to determine which domains of cognition are affected by OSA. This is because of marked differences in the nature of these reviews (e.g. many are unsystematic) and the many different tasks and domains assessed. This paper addresses this issue by comparing the results of only systematic reviews or meta-analyses assessing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
273
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(283 citation statements)
references
References 58 publications
5
273
2
3
Order By: Relevance
“…Also, several studies over years have shown an indirect association between excessive daytime sleepiness and the development of cognitive decline (Jaussent et al, 2012;Keage et al, 2012). Additionally, beneficial effects of treatment of OSA, on cognitive performance, vigilance and excessive daytime sleepiness have been shown in recent meta-analyses (Marshall et al, 2006;Olaithe et al, 2014) and a meta review (Bucks et al, 2013). These data have recently been extended to show the beneficial effects of the CPAP therapy on excessive daytime sleepiness in older OSA patients (McMillan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Also, several studies over years have shown an indirect association between excessive daytime sleepiness and the development of cognitive decline (Jaussent et al, 2012;Keage et al, 2012). Additionally, beneficial effects of treatment of OSA, on cognitive performance, vigilance and excessive daytime sleepiness have been shown in recent meta-analyses (Marshall et al, 2006;Olaithe et al, 2014) and a meta review (Bucks et al, 2013). These data have recently been extended to show the beneficial effects of the CPAP therapy on excessive daytime sleepiness in older OSA patients (McMillan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Kod pacijenata sa nedijagnostikovanom ili nelečenom OSA se javljaju i poremeća-ji neurokognitivnih funkcija u domenu pažnje, memorije i izvršnih funkcija [41], što dovodi do problema u svakodnevnim aktivnostima. Opada radna sposobnost, uz porast rizika od povređivanja na radu (relativni rizik 2,88) i odsustvovanja sa posla [42,43].…”
Section: Opstruktivna Apneja U Spavanju (Osa)unclassified
“…Sleep fragmentation is thought to lead to attention/vigilance dysfunction while global cognitive dysfunction may result from intermittent nocturnal hypoxemia [71]. OSA has been suggested to be a possible predisposing factor for delirium [72].…”
Section: Mechanisms For Neurocognitive Complicationsmentioning
confidence: 99%